Circulating annexin A5 predicts mortality in patients with heart failure. (30th July 2015) - Schurgers, L. J.; Burgmaier, M.; Ueland, T.; Schutters, K.; Aakhus, S.; Hofstra, L.; Gullestad, L.; Aukrust, P.; Hellmich, M.; Narula, J.; Reutelingsperger, C. P.
Abstract: Background: Natriuretic peptides are currently used to predict mortality in patients with heart failure (HF). However, novel independent biomarkers are needed to improve risk stratification in these patients. We hypothesized that annexin A5 (anxA5) would be highly expressed by organs which are generally affected by HF and that circulating anxA5 levels would predict mortality in HF patients. Methods: We prospectively determined the diagnostic value of anxA5, N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP), C‐reactive protein (CRP) and estimated glomerular filtration rate (eGFR) to predict mortality in 180 HF patients during a median follow‐up of 3.6 years. Studies were conducted with anxA5 −/− mice to investigate the underlying mechanisms. Results: AnxA5 levels were significantly elevated in HF patients compared to healthy control subjects. Cox regression analysis demonstrated that anxA5, NT‐proBNP and eGFR all predict mortality independently. AnxA5 significantly improved the diagnostic efficiency of NT‐proBNP alone (improvement of c ‐statistic from 0.662 to 0.705, P < 0.001) and also combined with eGFR and CRP (improvement of c ‐statistic from 0.675 to 0.738, P < 0.001) to predict mortality in the Cox regression model. Receiver operating characteristic curve analysis showed that anxA5 predicted 3‐year survival (area under curve 0.708) with an optimal cut‐off value of 2.24 ng mL −1 . Using anxA5 −/− mice, we demonstrated that anxA5 is highly expressed in organs that are often affected by HF including lung, kidney, liver and spleen. Lysis of these organs in vitro resulted in a marked and significant increase in anxA5 concentrations. Conclusion: AnxA5 improves the diagnostic efficiency of conventional biomarkers to predict mortality in HF patients. Whereas natriuretic peptides originate from the myocardium, high circulating anxA5 levels in patients with HF are likely to reflect peripheral organ damage secondary to HF.